Analisis Keragaman Genetik 161 Aksesi Mangga Indonesia Menggunakan Marka Mikrosatelit - Tasliah, Tasliah; Rijzaani, Habib; Hariyadi, Tri Z. P.; Yuriyah, Siti; Rebin, Rebin; Ma; Silitonga, Tiur S. (Jurnal AgroBiogen, 2013)
Mango is one of the fiveimportant fruit crops in the world. Microsatellite markers canbe used to analyze genetic diversity among mangoaccessions. The purpose of this research was to determinethe relationship among mango germplasm collection usingmicrosatellite markers. A total of 161 mango accessionsoriginated from Indonesian Tropical Fruit Research Institute(Cukurgondang Field Station), Pasuruan, East Java, wereused in this research. Twenty-six microsatellite markerswere used to genotype each accession. Genotyping wasconducted using Beckman CoulterÂ® CEQâ„¢ 8000 machine.Genetic relationship among accecions was analyzed usingthe Unweighted Pair Group Method with Arithmetic Mean(UPGMA) method, followed by bootstrap analysis. The resultshowed that high allele variation (15-75 alleles) wasobserved among mango accesions tested, with an averageallele number of 38.69. The average of PolymophismInformation Content (PIC) value was 0.548 (0.021-0.949).Fifteen microsatellite markers showed PIC value >0.5indicated that these markers were suitable for mangodiversity studies. Cluster analysis divided the mangocollections into two groups. Group I consisted of 95accessions, and group II consisted of 66 accessions. NinetyIndonesian indigenous mangos (84.11% of Indonesianmango accessions) could be separated from the introducedaccessions.